TRADISI RUWAHAN DAN PELESTARIANNYA DI DUSUN GAMPING KIDUL DAN DUSUN GEBLAGAN YOGYAKARTA - Purwanti, Rosalia Susila (Indonesian Journal of Conservation, 2014)
Ruwahan in Gamping Kidul Village and Geblagan Village is a form of culture preservation towards the tradition that has been held by the two villages, two subdistrics, and two regencies in the Special Region of Yogyakarta since 1984. The existance of this joint ruwahan tradition aims to strengthen the brotherhood between the two neighboring villages by working together to clean the tomb, holding kenduri feast of which foods brought from home by residents, as well as praying for ancestor spirits, especially, those who are buried in the cemetery nearby. Ruwahan tradition was carried out once a year in ruwah, a name of a month in Javanese calendar. Ruwahan tradition is served to pray for the ancestors in the afterlife, so that they can live in peace in heaven and the heirs are protected by their ancestors. The study concluded that the joint Ruwahan of the two villages started with the preparation, then it was held together by people whose ancestors buried in the Gamping Kidul dan Geblagan cemetry. The people will gather around in place where the ceremony was held without beng invited. During the preparation for the Ruwahan ceremony, good communication and mutual cooperation are established among the neighbouring villagers. They pray and praise their prophet in Javanese language. Keywords: ruwahan, traditions, cultural preservation Ruwahan di Dusun Gamping Kidul dan Dusun Geblagan Suatu Pelestarian Tradisi merupakan upacara adat-tradisi yang dilaksanakan oleh dua dusun, dua kelurahan, dua kabupaten di wilayah Daerah Istimewa Yogyakarta yang sudah berlangsung sejak tahun 1984. Bergabungnya tradisi ruwahan ini bertujuan untuk mempererat persaudaraan antara dua dusun yang berdekatan, bergotong royong untuk membersihkan makam, bersedekah kenduri yang dibawa dari rumah masing-masing warga, mendoakan bersama para arwah leluhur khususnya yang dimakamkan pada makam tersebut. Tradisi Ruwahan ini dilaksanakan satu tahun sekali pada bulan Ruwah. Tradisi Ruwahan ini menjadi tradisi yang berfungsi untuk mendoakan para leluhur agar di alam baka dapat hidup tenteram mulia di surga dan anak keturunannya dilindungi oleh para leluhurnya. Hasil penelitian menyimpulkan bahwa dengan Ruwahan gabungan dua dusun ini mulai dari persiapan sampai pelaksanaan para warga yang merasa memiliki leluhur di makam Gamping Kidul dan Geblagan ini meskipun tidak diundang mereka sadar untuk hadir. Dengan kebersamaan selama persiapan sampai pelaksanaan tradisi Ruwahan ini terjalin komunikasi, gotong royong antar para warga dusun yang berdekatan ini berdoa dengan cara bersholawat Jawi.Kata kunci: ruwahan, tradisi, pelestarian budaya